GEOGRAPHICAL ANALYSIS OF RURAL TERRITORIES OF ARARAT NATURAL ECONOMIC REGION (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
In the current article the analysis of prerequisites for forming and developing of rural territories of Ararat natural economic region of Armenia is presented, particularly concerning rural settlements and distribution of population. Issues concerning territorial differences and peculiarities of rural territories are discussed. Dynamics of population and settlements count in the region is presented for 1926–2015. Actual socioeconomic problems of rural territories of the region are highlighted.
Keywords: рural terrain; rural settlements; rural resettlement mountain regions; territorial resources